Front Matter JEMT Vol 1, No 1 (2020) - Editor editor (Lembaga Penelititan dan Pengabdian kepada Masyarakat - Institut Teknologi Adhi Tama Suraba, 2020)
This document contains cover, editorial board, and list of content